CompTIA PenTest+ Study Guide Exam PT0-001 - Chapple, Mike 1975-; Seidl, David 1971- (Sybex, 2019)
Front Matter -- Penetration Testing -- Planning and Scoping Penetration Tests -- Information Gathering -- Vulnerability Scanning -- Analyzing Vulnerability Scans -- Exploit and Pivot -- Exploiting Network Vulnerabilities -- Exploiting Physical and Social Vulnerabilities -- Exploiting Application Vulnerabilities -- Exploiting Host Vulnerabilities -- Scripting for Penetration Testing -- Reporting and Communication -- Get Certified! -- Comprehensive Online Learning Environment
Includes index. - Online resource; title from PDF title page (EBSCO, viewed October 19, 2018)
Keywords: Computer security / Study guides / Examinations; Penetration testing (Computer security) / Study guides / Examinations; Hackers / Study guides / Examinations; Computer networks / Study guides / Examinations; Hackers / Examinations / Study guides; Computer networks / Examinations / Study guides; Penetration testing (Computer security) / Examinations / Study guides; Computer security / Examinations / Study guides; Computer security; Examinations; Study guides; COMPUTERS; Security; General; Computer networks; Examinations; Electronic books; Electronic books / Study guides